Effect of fundamental stage training program based on LTAD model toward basic swimming skills - Arifin, Z.; Permadi, A. A.; Pratiwi, R. A. (Advances in Social Science, Education and Humanities Research, 2020)
The purpose of the study is to find the effect of a fundamental stage training program on basic swimming skills. Pre-experimental design with one-group pretest-posttest design was employed as the research method. The population of this study was 20 students of TK IT Al-Wasilah who are 6 years old. Meanwhile, the sample of the study was taken as a whole of the population (saturated sample). The research instrument was a basic swimming skills test. The data obtained will be analyzed using paired sample t-test analysis. The result showed that there is a significant Effect of Fundamentals Stage Training Program Based on LTAD Model towards Basic swimming skills.